1990
DOI: 10.1111/j.1467-9892.1990.tb00048.x
|View full text |Cite
|
Sign up to set email alerts
|

A Distance Measure for Classifying Arima Models

Abstract: In a number of practical problems where clustering or choosing from a set of dynamic structures is needed, the introduction of a distance between the data is an early step in the application of multivariate statistical methods. In this paper a parametric approach is proposed in order to introduce a well-defined metric on the class of autoregressive integrated moving-average (ARIMA) invertible models as the Euclidean distance between their autoregressive expansions. Two case studies for clustering economic time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
140
0
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(146 citation statements)
references
References 7 publications
0
140
0
6
Order By: Relevance
“…Piccolo (1990) proposed a metrics measuring the distance between two ARMA models, based on the comparison of the coefficients of their AR(∞) representation. This tool has had a large success in several fields; a review of its properties and applications with several references can be found in Piccolo (2007) and Corduas and Piccolo (2008).…”
Section: Unconditional Minimum and Time-varying Volatilitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Piccolo (1990) proposed a metrics measuring the distance between two ARMA models, based on the comparison of the coefficients of their AR(∞) representation. This tool has had a large success in several fields; a review of its properties and applications with several references can be found in Piccolo (2007) and Corduas and Piccolo (2008).…”
Section: Unconditional Minimum and Time-varying Volatilitiesmentioning
confidence: 99%
“…In particular, he distinguishes three major categories of approaches to time series clustering: 1) raw-data-based approaches, in which the series compared are considered as normally sampled at the same interval; 2) features-based approaches, in which the series are compared using some selected features; 3) model-based methods, where the time series are considered similar when the models characterizing them are similar. The approach proposed in this work belongs to the third category; in particular it follows the tradition of AR processes to capture the similarity among time series, as in Piccolo (1990), Maharaj (1996Maharaj ( , 1999Maharaj ( , 2000, Xiong and Yeung (2002) (see Piccolo, 2007, and Corduas and Piccolo, 2008, for a review). Most of these studies are devoted to capturing the structure of the mean of the process hypothesized as generator of the data, whereas little attention was put on the variance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the above example, when online users are modelled as mixture of Markov chains, each user is represented by a vector consisting of the transition probabilities of the underlying Markov chain, and then the clusters can be obtained based on similarity between the estimates of transition probabilities for different users [2,7]. Similarly, when the sales pattern of an item is modelled as a mixture of time series, the clusters of items can be obtained based on similarity between the estimates of the time series parameters for each item [22,24]. Another example is clustering of similar stocks based on their β values that can be obtained by using ordinary linear regression (the Capital Asset Pricing Model) on the observed stock prices [16].…”
Section: Motivation For Clustering Of Model Parametersmentioning
confidence: 99%